Study on characterization of bio-oil derived from sugarcane bagasse (Saccharum barberi) for application as biofuel. Issue 2 (5th March 2022) - Kabir Ahmad, Syahirah Faraheen; Md Ali, Umi Fazara; Md Isa, Khairuddin; Gopinath, Subash C B
Abstract: Lignocellulosic biomass especially, sugarcane bagasse Saccharum barberi sp., appears to be a more suitable material for partial substitution of transport fuel (diesel) than Saccharum officinarum sp., due to its structural similarity to transport fuel (diesel). Besides that, less research has been implemented on this type of species. Bio-oil can be implemented as biodiesel by processing it further using chemical reactions such as hydrodeoxygenation and cracking with zeolite catalyst. Hence, the purpose of this study is to determine the compatibility of pyrolytic bio-oil produced from Saccharum barberi sp. in comparison with S. officinarum sp. for use as transport fuel (diesel) in automotive applications. This purpose can be accomplished by comparing the oil's bio-physiochemical properties for both species. The experiment is conducted on a bench-scale on which bio-oil of Saccharum barberi sp. is secured from the catalytic pyrolysis process at a temperature of 500°C and heating rate of 50°C/min with the addition of ZSM-Zeolite catalyst. Thermogravimetric analysis of Saccharum barberi sp. reveals that cellulose is more reactive than lignin, evidenced by the high percentage of weight loss at temperatures ranging from 251°C to 390°C. The high contents of carbon (40.7%) and hydrogen (6.50%), as well as slight traces of sulphur (0.08%) and nitrogen (0.85%), in bio-oil ( Saccharum barberi sp.) indicate that it is conceivable to be partially used for replacement in biofuel production. Overall physiochemical properties reveal that Saccharum barberi sp. shows more potential than S. officinarum sp. Gas chromatography–mass spectrometry analysis reveals that bio-oil consists of high amounts of aromatic hydrocarbon (26.2%), phenol (14.8%) and furfural (13.0%) in comparison to S. officinarum sp. Biofuel was produced from sugarcane bagasse ( Saccharum barberi sp.) in a bench-scale pyrolysis reactor at 500°C using a zeolite catalyst. Measured properties of the biofuel make it suitable for partial substitution of diesel in transport fuel. Abstract : Biofuel was produced from sugarcane bagasse ( Saccharum barberi sp.) in a bench-scale pyrolysis reactor at 500Ã‚Â°C using a zeolite catalyst. Measured properties of the biofuel make it suitable for partial substitution of diesel in transport fuel. Graphical Abstract: